2010
DOI: 10.3109/02699052.2010.511589
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic strength training of lower limb muscles following acquired brain injury

Abstract: Isokinetic strength training may be effective to improve lower limb muscle strength; however, care needs to be taken in selecting suitable candidates as some individuals reported knee pain with this intensive programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The strengthening program may have also contributed to increased muscle tone. 23,24 Several authors 25,26 have reported that decreased muscle tone contributes to increased laxity. Therefore, having cheerleaders participate in a strength and conditioning program may reduce laxity and increase stiffness during the course of a competitive season.…”
Section: Discussionmentioning
confidence: 99%
“…The strengthening program may have also contributed to increased muscle tone. 23,24 Several authors 25,26 have reported that decreased muscle tone contributes to increased laxity. Therefore, having cheerleaders participate in a strength and conditioning program may reduce laxity and increase stiffness during the course of a competitive season.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory muscle training has not been evaluated among people with TBI. While ballistic (Williams, Clark, Hansson, & Paterson, 2014) and isokinetic (Killington, Mackintosh, & Ayres, 2010) strength training has been investigated in this population, changes in cardiorespiratory fitness were not evaluated.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%